PENGARUH BAKTERI PSIKROTROF TERHADAP MUTU GIZI SUSU SEGAR - Heru Yuniarti; Mirnawati B. Sudarwanto; R. Roso Soejoedono; Komari Komari (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1999)
The objective of the research was to study the presence of psychrotropic bacteria in fresh milk and its effect on the quality of fresh milk stored at 7 derajat celcius. The samples were collected from Koperasi Pengumpil Susu (Milk Collecting Cooperation, KPS) in Bogor. On the preliminary study, the fresh milk was analyzed for macro-nutrients. Total count and psychrotropic bacteria were determined. Total count of bacteria in fresh milk was 1.5 x 106 colony forming unit (cfu)/ml and the psychrotropic bacteria was 2.7 x 104 cfu/ml or 1.9%. This total count bacteria was normal and the nutrient content was close to the standard (DSN). On the main study, psychrotropic bacteria was added (1004 cfu/ml) into the pasteurized milk to evaluate its growth at low temperature, and chemical changes during the milk storage for 0, 24, 48 and 72 hours. The result showed that the growth of bacteria was higher on milk added with the bacteria. There were changes on the quality of the fresh milk during storage, but these changes were not significantly different.Keywords: psychrotropic bacteria, fresh milk, nutritional anality, nutrient content